Diversity and characteristics of mangrove vegetation in Pulau Rimau Protection Forest, Banyuasin District, South Sumatra, Indonesia - ERNIK YULIANA; YUNI TRI HEWINDATI; ADI WINATA; WIBOWO A DJATMIKO; ATI RAHADIATI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Yuliana E, Hewindati YT, Winata A, Djatmiko WA, Rahadiati A. 2019. Diversity and characteristics of mangrove vegetation in Pulau Rimau Protection Forest, Banyuasin District, South Sumatra, Indonesia. Biodiversitas 20: 1215-1221. The purpose of the study was to analyze the flora diversity and characteristics of mangrove vegetation in Pulau Rimau Protection Forest, Banyuasin District, South Sumatra. Data collected were the number and girth diameter of mangrove tree species, and aquatic ecology parameters using transect method. The sample plots size were 2m×2 m; 5m×5 m; 10m×10 m; for seedling, sapling, and tree, respectively. The observation plots were arranged in a row of 120 m length on two sides of the forest edge, namely Calik Riverbank and Banyuasin Riverbank. Data were analyzed using importance value index (IVI), Simpson’s diversity index and Sørensen’s community similarity. The study revealed that there were differences in mangrove characteristics in two study sites. There were 57 plant species identified inside and outside sample plots, but only 15 species (26.32%) among them were categorized as true mangrove species. Inside the sample plots, there were 11 and 10 mangrove tree species recorded on the Calik Riverbank and Banyuasin Riverbank, respectively, but only 7 species among them were found in both sites. The mangroves on Calik Riverbank were dominated by Nypa (IVI 53.59%) and Bruguiera (51.12%), while those on Banyuasin Riverbank were dominated by Sonneratia (66.91%) and Avicennia (51.73%). The Simpson’s diversity index for Calik Riverbank and Banyuasin Riverbank was 0.82 and 0.78, respectively, whereas the Sørensen’s coefficient of community between the two sites was 0.67.